2017
DOI: 10.1038/emm.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

hMSCs suppress neutrophil-dominant airway inflammation in a murine model of asthma

Abstract: Although chronic eosinophilic inflammation is a common feature in patients with asthma, some patients have neutrophil-dominant inflammation, which is known to be associated with severe asthma.Human mesenchymal stem cells (hMSCs) have shown promise in treating various refractory immunological diseases. Thus, hMSCs may represent an alternative therapeutic option for asthma patients with neutrophil-dominant inflammation, in whom current treatments are ineffective. BALB/c mice exposed to ovalbumin and polyinosinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
(50 reference statements)
0
28
0
Order By: Relevance
“…In previous studies, a single dose of MSCs administered prophylactically or therapeutically reduced lung influx of inflammatory cells, airway hyperresponsiveness, and mucus hypersecretion in models of ovalbumin-induced allergic asthma. 3,7,8,22,23 In HDM-induced allergic asthma, a single dose of MSCs administered prophylactically also prevented inflammation by modulating epithelial cell activation. 24 However, effects on the inflammatory process were only marginal, with no improvements in lung function and remodeling when MSCs were administered therapeutically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, a single dose of MSCs administered prophylactically or therapeutically reduced lung influx of inflammatory cells, airway hyperresponsiveness, and mucus hypersecretion in models of ovalbumin-induced allergic asthma. 3,7,8,22,23 In HDM-induced allergic asthma, a single dose of MSCs administered prophylactically also prevented inflammation by modulating epithelial cell activation. 24 However, effects on the inflammatory process were only marginal, with no improvements in lung function and remodeling when MSCs were administered therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stromal cell (MSC) therapy has demonstrated promising results in several lung disease models, but its impact on airway remodeling has been sometimes controversial . In models of ovalbumin‐ and Aspergillus hyphal extract‐induced allergic asthma, a single dose of MSCs administered either locally or systemically resulted in reduction of both lung inflammation and remodeling . Conversely, in house dust mite extract (HDM)‐induced allergic asthma, a single dose of MSCs reduced some inflammatory parameters but was unable to ameliorate lung function or remodeling .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil infiltration into the airways and lung parenchyma is a hallmark event in acute pulmonary inflammation, and typifies a wide range of human lung diseases, including asthma, chronic obstructive lung disease, and pneumonia [29] , [30] . In the present work, the involvement of (bi)sulfite-induced free radicals in LPS-induced lung inflammation was evaluated in mice.…”
Section: Discussionmentioning
confidence: 99%
“… 11 It is widely accepted that transcriptional regulation plays a pivotal role in IL-10 gene expression. 11 , 26 Indeed, ERK-dependent transcription activity mechanisms in IL-10 production have been demonstrated. 27 A number of studies have reported that IL-33 activates MAPKs, but to the best of our knowledge, no study has explored the relationship between IL-33-induced MAPK activation and IL-10 expression.…”
Section: Discussionmentioning
confidence: 99%